Youth Pledge: Pillars of Unity in the Indonesian National Movement - Deswita, Nadya; Eva , Christin; Steven , Rinaldi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The Youth Pledge is a historic moment in the journey of the Indonesian national movement which played an important role in uniting various movement organizations. Through a pledge to one homeland, one nation and one unified language, the Youth Pledge encourages a spirit of unity among youth from various backgrounds. With the spirit of unity inspired by the Youth Pledge, various national movement organizations united to achieve the ideals of Indonesian independence. The principles expressed in the Youth Pledge form a strong ideological foundation for the national movement, influencing the focus and direction of the national movement organization to further emphasize unity. Organizations such as Budi Utomo, Sarekat Islam, and Indische Partij, which emerged before and after the Youth Pledge, further strengthened their commitment to the unity of the Indonesian nation. In addition, the Youth Pledge helps build Indonesia's national identity by adopting Indonesian as the language of unity, as well as fostering solidarity among Indonesian youth in the face of colonial oppression. The period of national movement in Indonesia lasted from the founding of Budi Utomo in 1908 until the collapse of the Dutch colonial government. During this period, the Indonesian people attempted to free themselves from colonialism with the aim of achieving independence, sovereignty, justice and prosperity. This solidarity is reflected in various resistance movements and political actions carried out by national movement organizations after the Youth Pledge. Thus, the Youth Pledge is not only a historical moment, but also an important milestone in uniting various organizations of the Indonesian national movement towards the ideals of independence.